Literature Review of The Role of Self-Talk in Counseling on Its Impact on Emotional Regulation and Well-Being - Fauzi Aldina; Reza Muttaqin (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Self-talk is a critical cognitive process that influences emotional regulation, mental health, and overall well-being, making it a valuable tool in counseling practices. This study employs a Systematic Literature Review (SLR) approach to examine the role of self-talk in therapeutic settings, focusing on its impact on emotional regulation and psychological resilience within frameworks such as Cognitive Behavioral Therapy (CBT) and Rational Emotive Behavior Therapy (REBT). A total of 28 peer-reviewed articles published between 2010 and 2024 were systematically analyzed using PRISMA guidelines to identify thematic trends and empirical patterns. The findings reveal a consistent increase in research on self-talk interventions over the last decade, highlighting their effectiveness in enhancing emotional stability, reducing anxiety and depression, and improving coping strategies. However, challenges remain in terms of clients’ resistance to cognitive restructuring, subjective variability in self-talk measurement, and the lack of standardized assessment tools. Future studies are encouraged to explore technology-based interventions and cross-cultural adaptations to improve accessibility and personalization. Keywords: self-talk, counseling, emotional regulation, cognitive behavioral therapy, mental health